Sustainable mining development in Aceh Besar, Indonesia: A challenge and solution (Banda Aceh, 2013) - Elviandi Rs; Nor Malina Malek (Proceedings of AICS - Social Sciences, 2013)
Mining sector is a natural resource that takes a long time to do exploitation. Mining activity is also a sector that has a great impact on development in an area such as economic, social and environmental. Therefore, the concept of sustainable mining development should be directed to achieve three objectives, namely economic development, social andenvironmental. Economic purpose is not only to focus on the macro-economic growth alone, but must consider the economic conditions of local communities. Then pay attention to social goals must be the local social and cultural conditions so that welfare can be improved. Further environmental objectives must considerthe balance of the environment around the mining activity. The amount of growth in the mining sector on development in the province especially in Aceh Besar district can be seen from the Gross Domestic Regional Product (GDRP). This sector has a major role to both the local economy and the growth conditions of the local communities. But the concept of sustainable development is not only economic growth alone is the target of development of a region. According to data from the Department of Mines and Energy of the Province of Aceh in 2011, there were six (6) mining companies operating in Aceh Besar regency which has contributed greatly to the GDP of Aceh Besar district. However, the selection of research sites only in existing mining companies in the district Lhoong as a case study because of the attention to the criteria of the concept of sustainable development. The results showed that the mining activity in the area during this study generated a lot of negative impressions for both regional and local communities. Aceh post-tsunami and post-conflict between the Government of Indonesia and the Free Aceh Movement (GAM), a lot of investors who built the company's mining sector in Aceh Besar district, but the potential is very big problem will arise if the problems that exist today cannot be solved immediately. Ecological damage caused by the efforts of development and economic growth has provided a real threat. The condition raises concerns about the sustainability of resources for future generations in Aceh Besar district.Therefore, by introducing the concept of sustainable development of mining this is a solution to overcome the problems of existing mines in the province especially in Aceh Besar district.Keywords: Sustainable Mining, economic, social, environmental, Aceh Besar